Evaluation of cognitive and psychomotor faculties in relation to mood-related symptoms under the conditions of sleep deprivation - Marcin Sochal; Marta Ditmer; Piotr Białasiewicz; Szymon Turkiewicz; Filip Franciszek Karuga; Agata Gabryelska (Frontiers in Psychiatry)
IntroductionDeprivation of sleep (DS) has been associated with changes in mood and cognitive function, rapidly but transiently improving the severity of depression symptoms. However, it remains unclear whether there are differences in performance between DS responders and non-responders. The relationship between DS, mood, cognitive, and psychomotor function is also poorly understood.MethodsParticipants (n = 77) underwent a baseline assessment of sleep under the control of polysomnography (PSG). Later they were subjected to DS with actigraphy monitoring. Evaluation of mood as well as completing a battery of tests assessing cognitive functions and eye-hand coordination was conducted four times, pre/post PSG and DS. Participants were further divided into respondents (RE, n = 48) and non-respondents (NR, n = 29) depending on alleviation of depression symptoms severity following DS.ResultsAll participants exhibited increased response speed to visual triggers after DS compared to baseline (p = 0.024). Psychomotor vigilance test (PVT) results remained intact in the RE, whereas it was increased in the NR (p = 0.008). Exposure time in the eye-hand coordination test improved in both groups, but total error duration was reduced only in RE individuals (p < 0.001, p = 0.009 for RE and NR, respectively). All subjects were more proficient at trail-making test (p ≤ 0.001 for Part 1 and 2 in all, NR, RE). Stroop test also improved regardless of mood changes after DS (p = 0.007, p = 0.008 for Part 1 and 2, respectively); cognitive interference remained at a similar level within groups (p = 0.059, p = 0.057 for NR and RE, respectively). A positive correlation was observed between the difference in PSG morning/DS morning depression severity and vigilance (R = 0.37, p = 0.001, R = 0.33, p = 0.005, for error duration eye-hand coordination test and PVT total average score, respectively).ConclusionRE tend to maintain or improve cognitive function after DS, oppositely to NR. Vigilance in particular might be tightly associated with changes in depression symptoms after DS. Future studies should examine the biological basis behind the response to sleep loss.